UM SERVIÇO BASEADO EM ALGORITMOS GENÉTICOS PARA PREDIÇÃO DA BOLSA DE VALORES - Nascimento, Thiago Pinheiro do (2015)
To anticipate the stock exchange pricing is not considered a simple task, because involves many obscure variables, which must be able to represent the real marketplace situation. This is a fundamental reason for the investors lose money and end up giving up investing in the capital market. In an attempt to address this issue, this paper proposes the development of a servisse capable of estimating the future price of assets in the Stock Exchange. For this, it used of a genetic algorithm, which allows to extract features from the market, necessary for estimating the future behavior of an action.